Complexation of ibuprofen with water soluble p-sulfonatocalix [4] arene: A potential candidate for drug delivery application - Khokhar, Tahira S.; Memon, Shahabuddin; Panhwar, Qadeer K.; Memon, Fakhar N.; Memon, Ayaz A.; Samejo, Muhammad Qasim; Muneer, Saba; Tulu, Metin (UNIV KARACHI, 2017)
Complexation of ibuprofen with water soluble p-sulfonatocalix[4]arene (3) was evaluated. Both molecules exhibit a host and guest type complexation. pH, complex stoichiometry and binding constant were determined by UV-Vis and FT-IR spectroscopy. The maximum complexation of 3 with ibuprofen occurs at pH 2. Stability constant values (9.897) show that there is favorable complex formed due to vital role of p-sulfonatocalix[4]arene, while the thermodynamic parameters, i.e. Delta Q Delta H and Delta S have been found as -24.09 KJ/mol, 0.012 KJ/mol and 0.12 KJ/mol. K, respectively. The results show that 3 has efficiency to carry the drug at particular conditions and can be used for drug delivery as a carrier.
Keywords: Synthesis; inclusion complex; p-sulfonatocalix[4]arene; thermodynamic; drug delivery; RELEASE; RECOGNITION; CALIXARENES; DERIVATIVES; Pharmacology & Pharmacy